(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Fungal infections like oral candidiasis is prevalent in cancer patients as their immune systems were compromised.Material and Methods: 377 cancer patients who were clinically diagnosed with oropharyngeal candidiasis were included in the study. Isolation and identification of Candida species was based on standard microbiological procedures. CLSI (2021) recommendations were followed when determining antifungal susceptibility.Results: Among the total 377 cases included, the highest number of instances was reported in those aged 41 to 50 years (30.23%). Candida albicans (21.98%) was the most frequent followed by Candida tropicalis (18.84%), Candida prapsilosis (17.80%). Monomicrobial growth was observed in 77.63% patients whereas polymicrobial growth was observed in 22.36% patients. Candida albicans (24.59%) and Candida tropicalis (20.49%) were the most frequent isolates among patients who underwent chemotherapy while Candida albicans (40%) and Candida Parapsilosis (26.66%) were the most frequent isolates among patients undergoing radiotherapy. Miconazole was found to be more susceptible than Fluconazole, Itraconazole, Clotriconazole among the antifungals.Conclusion: Due to the risk of a systemic infection, it is important to recognise candidiasis as soon as possible for the clinical management of seriously unwell cancer patients. It may also aid the clinician in selecting antifungals for empirical treatment.